IDENTITAS MULTIKULTURAL SALAM –SARANI DI MALUKU SEBAGAI MODEL MEMELIHARA INTEGRASI BANGSA - Eklefina Pattinama (Program Pascasarjana UKIM, 2020)
There are many ethnic and sub-ethnic groups, religions and ideologies in Ambon and Saparua islands. These pluralistic existences imply that differences are core part of the society which can become a strength to live together, but also threat to the society. Ironically, there is a tendency to manipulate these pluralistic existences to become provocative issue to raise tension in these societies. Therefore, the aim of this article is to study how pluralistic societies such as people in Ambon and Saparua islands maintain national integrity through strengthening multi-cultural identity. By conducting field research and library study, the researcher find out that in order to develop multi-cultural identity, one must has an ability to maintain self-narration. In the self-narration people must have ability to develop consistency awarneses about continuity of self-biography. Besides, the very basic principle of people in Ambon and Saparua islands to maintain national integrity is through their daily activities as anak negeri which has shaped their religious special identity as Salam-Sarani. There are many ethnic and sub-ethnic groups, religions and ideologies in Ambon and Saparua islands. These pluralistic existences imply that differences are core part of the society which can become a strength to live together, but also threat to the society. Ironically, there is a tendency to manipulate these pluralistic existences to become provocative issue to raise tension in these societies. Therefore, the aim of this article is to study how pluralistic societies such as people in Ambon and Saparua islands maintain national integrity through strengthening multi-cultural identity. By conducting field research and library study, the researcher find out that in order to develop multi-cultural identity, one must has an ability to maintain self-narration. In the self-narration people must have ability to develop consistency awarneses about continuity of self-biography. Besides, the very basic principle of people in Ambon and Saparua islands to maintain national integrity is through their daily activities as anak negeri which has shaped their religious special identity as Salam-Sarani.